The stereochemical course of the first step of pre-mRNA splicing. - Maschhoff, K L (1993)
We have determined the effects on splicing of sulfur substitution of the non-bridging oxygens in the phosphodiester bond at the 5' splice site of a pre-mRNA intron. Pre-mRNAs containing stereochemically pure Rp and Sp phosphorothioate isomers were produced by ligation of a chemically synthesized modified RNA oligonucleotide to enzymatically synthesized RAs. When these modified pre-mRNA substrates were tested for in vitro splicing activity in a HeLa cell nuclear extract system, the RNA with the Rp diastereomeric phosphorothioate was not spliced while the Sp diastereomeric RNA spliced readily. The sulfur-containing branched trinucleotide was purified from the splicing reaction of the Sp RNA and analyzed by cleavage with a stereospecific nuclease. The results showed that the Sp phosphorothioate was inverted during the splicing reaction to the Rp configuration; a finding previously obtained for a Group I self-splicing RNA. This inversion of configuration is consistent with a transesterification mechanism for pre-mRNA splicing. The lack of splicing of the Rp modified RNA also suggests that the pro-Rp oxygen at the 5' splice site is involved in a critical chemical contact in the splicing mechanism. Additionally, we have found that the HeLa cell RNA debranching enzyme is inactive on branches containing an Rp phosphorothioate.